1973
DOI: 10.4049/jimmunol.111.4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies and Soluble Antigen-Antibody Complexes by Precipitation with Polyethylene Glycol

Abstract: Polyethylene glycol (PEG) was used in a modification of the Farr antigen binding test in order to separate free antigen from antibody-bound antigen. Most of the immunoglobulins are precipitated at 20% PEG while smaller antigens like bovine serum albumin or insulin are quite soluble at this concentration of PEG. Such antigens are therefore precipitated in 20% PEG if they are bound to antibodies. Furthermore, PEG has been used at lower concentrations in order to precipitate soluble antigen-antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 361 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ICs can be precipitated from serum using PEG [13], and it was later confirmed that low concentrations of PEG selectively precipitate ICs with minimal free IgG, probably by steric hindrance effects [23,24]. Large proteins or complexes are precipitated by PEG by steric exclusion only if they are surrounded by linear PEG chains [25,26].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…ICs can be precipitated from serum using PEG [13], and it was later confirmed that low concentrations of PEG selectively precipitate ICs with minimal free IgG, probably by steric hindrance effects [23,24]. Large proteins or complexes are precipitated by PEG by steric exclusion only if they are surrounded by linear PEG chains [25,26].…”
Section: Introductionmentioning
confidence: 90%
“…Large proteins or complexes are precipitated by PEG by steric exclusion only if they are surrounded by linear PEG chains [25,26]. Although numerous methods are available for recovery of ICs by PEG precipitation [5,7,[23][24][25][26][27][28][29][30][31][32], very few studies have identified the antigen within ICs.…”
Section: Introductionmentioning
confidence: 99%